Deslocamentos e conexões: o feminismo (interseccional) em Maria Lacerda de Moura e Patrícia Galvão - Achre, Simone Pinheiro (2022)
Maria Lacerda de Moura and Patrícia Galvão were women of their time and ahead of it. They assumed an active role in political movements, criticizing patriarchal society, religion, and bourgeois feminism itself. The issues they raised remain current and can be read and discussed in view of the rich legacy they left behind. Thus, the general objective of this research was to read the available intellectual production of Moura and Galvão and, through this process, allow their voices to be heard by having their writings and their historical paths revisited to realize their contributions to women's writing in the Latin American context and their reverberations for intersectional feminism. The hypothesis formulated was that the feminisms of the authors understood the intersectional categories present in the social division and oppression of women, thus advocating contemporary intersectional feminism still at the beginning of the 20th century. The justification for this study was based on the need to deepen the analysis of issues related to the thought and contributions of Maria Lacerda de Moura and Patrícia Galvão to the feminist movement. The methodology was that of comparative analysis of the themes that emerged from the reading of some of the works available from these authors, in addition to bibliographical research, which allowed for a survey of the life and work of Moura and Galvão, as well as an understanding of their thought in relation to the historical period and context in which they lived. The main theorists that guided the analyses were: Silvia Molloy (2003), Michelle Perrot (2005, 2017), Margareth Rago (2007, 2014), Aleida Assmann (2011), Heleieth Saffioti (2013, 2015), Simone Beauvoir (2016), Djamila Ribeiro (2017), Eurídice Figueiredo (2017), Mary Del Priore (2017, 2020), Silvia Federici (2017), Lélia Gonzalez (2018, 2020), bell hooks (2019, 2020), Carla Akotirene (2019), Chimamanda Ngozi Adichie (2019), Márcia Tiburi (2020), and Patricia Hill Collins and Sirma Bilge (2021). The results obtained point out that by reading the intellectual production of the authors and knowing their lives, it is possible to see that the categories, social divisions, and oppression of women were already present in the authors' writing, for this reason, reading the works of Maria Lacerda de Moura and Patrícia Galvão are necessary for contemporaneity, given the timeliness of the themes and the reflective power that reading them elicits.